2022
DOI: 10.1021/acschemneuro.2c00448
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Hydroxylase 2 Knockout Male Rats Exhibit a Strengthened Oxytocin System, Are Aggressive, and Are Less Anxious

Abstract: The central serotoninergic system is critical for stress responsivity and social behavior, and its dysregulations have been centrally implicated in virtually all neuropsychiatric disorders. Genetic serotonin depletion animal models could provide a tool to elucidate the causes and mechanisms of diseases and to develop new treatment approaches. Previously, mice lacking tryptophan hydroxylase 2 (Tph2) have been developed, showing altered behaviors and neurotransmission. However, the effect of congenital serotonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Additionally, studies have demonstrated that TPH2 depletion led to more impulsivity and high aggressiveness [15]. Consistent with these reports, Tph2 -/male rats also displayed low levels of anxiety-like behavior and high levels of aggression during social interaction [17]. Consequently, the regulation of the 5-HT rate-limiting enzyme TPH2 and its impact on behavior is crucial for the development of effective treatments for these disorders.…”
Section: Introductionsupporting
confidence: 56%
“…Additionally, studies have demonstrated that TPH2 depletion led to more impulsivity and high aggressiveness [15]. Consistent with these reports, Tph2 -/male rats also displayed low levels of anxiety-like behavior and high levels of aggression during social interaction [17]. Consequently, the regulation of the 5-HT rate-limiting enzyme TPH2 and its impact on behavior is crucial for the development of effective treatments for these disorders.…”
Section: Introductionsupporting
confidence: 56%
“…In this context, it is known that mice without TPH2 are less anxious and show more social interaction, but social interaction shows elevated levels of aggression [99]. The first study to evaluate oxytocin levels in TPH -/-mice found increased oxytocin levels in the hypothalamus's prefrontal cortex and paraventricular nucleus [100]. Oxytocin in the prefrontal cortex reduces anxiety-like behaviour [101] and promotes social behaviour [102].…”
Section: Genetics Epigenetics and Tryptophan Metabolismmentioning
confidence: 99%
“…Oxytocin in the prefrontal cortex reduces anxiety-like behaviour [101] and promotes social behaviour [102]. Given the range of polymorphisms or deletions of serotonin synthesis enzymes or serotonin itself, other pathways with phenotypic plasticity may arise to keep appropriate serotonin levels, such as reduction of serotonin catabolism [103], as well as modification of other systems such as oxytocin [100].…”
Section: Genetics Epigenetics and Tryptophan Metabolismmentioning
confidence: 99%
“…Despite such a modest effect, modern neuroscientific tools keep pointing towards a serotonergic role in aggression. Since the discovery that the central nervous system has its own enzyme to synthesize serotonin (Tryptophan hydroxylase-2 (Tph-2); [ 106 ]), it was shown that a partial or complete knockdown led to more aggressive behavior in rodents [ 107 , 108 , 109 , 110 ] and could be linked to a diminished 5-HT 1A receptor sensitivity [ 111 ]. On the other hand, highly aggressive wild-derived mice had higher mRNA levels of Tph-2 than other laboratory animals [ 112 ].…”
Section: The Neurotransmission and Genetics Of Aggressionmentioning
confidence: 99%